2021
DOI: 10.1002/adma.202007581
|View full text |Cite
|
Sign up to set email alerts
|

Electron Density‐Change in Semiconductor by Ion‐Adsorption at Solid–Liquid Interface

Abstract: The change in electrical properties of electrodes by adsorption or desorption at interfaces is a well‐known phenomenon required for signal production in electrically transduced sensing technologies. Furthermore, in terms of electrolyte–insulator–semiconductor (EIS) structure, several studies of energy conversion techniques focused on ion‐adsorption at the solid–liquid interface have suggested that the electric signal is generated by ionovoltaic phenomena. However, finding substantial clues for the ion‐adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Based on the above results, we confirmed that the carrier concentration of PCNF played a crucial role in the electricity generation during water infiltration, and its effect was verified by the ionovoltaic effect [8,[11][12][13][14][15] accurately. The ionovoltaic effect refers to the electricity generation by the change in surface properties via ion dynamic motions, such as ion adsorption.…”
Section: Mechanism Of Water-infiltration-induced Electricity Generationmentioning
confidence: 53%
See 1 more Smart Citation
“…Based on the above results, we confirmed that the carrier concentration of PCNF played a crucial role in the electricity generation during water infiltration, and its effect was verified by the ionovoltaic effect [8,[11][12][13][14][15] accurately. The ionovoltaic effect refers to the electricity generation by the change in surface properties via ion dynamic motions, such as ion adsorption.…”
Section: Mechanism Of Water-infiltration-induced Electricity Generationmentioning
confidence: 53%
“…Herein, we verified the effect of semiconductor carrier concentration, a crucial factor on electricity generation during water infiltration. By comprehensively investigating this factor on electricity generation, we accurately demonstrated the energy harvesting mechanism of the ionovoltaic effect [8,[11][12][13][14][15] via energy band theory in semiconductors. Briefly, the behavior of ions adsorption on the nanostructured semiconductor surface altered its carrier concentration, which induced a potential difference between wet and dry regions and generated electrical energy.…”
Section: Introductionmentioning
confidence: 99%
“…line with various water-motion-induced electricity-generating phenomena, ion dynamics in the electrolyte can induce spatially asymmetric potential in the semiconductor, an electromotive force for electricity generation. [20] However, understanding and controlling the ionovoltaic effect in semiconducting materials remains imperative since multipronged influences of these dipole potential effects from the electrolyte part to the electrode layer were raised as indispensably investigating areas. [16,17,22] In this study, the interfacial potential effect of the surficial molecular layer in the ESS structure was investigated through an ionic diffusion-induced ionovoltaic transducer (IIT).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, this was experimentally proved through a liquid‐adjoining Hall measurement in ESS structure, which verified that the ion adsorption on SAM could offer a self‐gating (without an external gate potential) effect, thereby accumulating charge carriers at the SAM–semiconductor interface. [ 2 , 20 ] These results suggested that, as the semiconductor has a less charge screening capability than a metallic electrode, it can sensitively vary its charge carrier density near the SAM–semiconductor interface depending on the electrolyte condition. [ 2 , 21 ] Hence, in the same line with various water‐motion‐induced electricity‐generating phenomena, ion dynamics in the electrolyte can induce spatially asymmetric potential in the semiconductor, an electromotive force for electricity generation.…”
Section: Introductionmentioning
confidence: 99%
“…[11,15,16] As a discerning method of solid/liquid interfacial states, an ionovoltaic generation, converting the interfacial potential effects on the electrolyte/dielectric (SAM and insulating layer)/electrode interface to electric signals, has been proposed, and correlative studies were conducted for investigating its mechanism. [17][18][19][20][21] The interfacial potential gradient, emanating from the intrinsic molecular dipole of SAM, was revealed to an origin of electric signals, and through this, such a system was demonstrated to sensitively probe the interfacial potential alteration by chemical interactions within the electrolytes/SAM interface (e.g., de-/protonation and ion complexation). [9,22] Hence, along with varying the SAM design, specific ion-molecular interactions at the liquid/ SAM interface could be interrogated through an intuitive observation of electrical output changes on the ionovoltaic system.…”
Section: Introductionmentioning
confidence: 99%